2023
DOI: 10.2147/prbm.s411112
|View full text |Cite
|
Sign up to set email alerts
|

The Nonlinear Relationship Between Body Mass Index (BMI) and Perceived Depression in the Chinese Population

Abstract: Purpose Existing studies on the association between BMI and depression report conflicting results with some demonstrating a positive relationship, while others a negative link or insignificant correlation. Very limited research on the nonlinear relationship between BMI and depression has yet to clarify the reliability and robustness of the potential nonlinearity and whether a more complex association exists. This paper aims to systematically investigate the nonlinear relationship between the two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 111 publications
2
3
0
Order By: Relevance
“…In obese patients, however, levels of leptin are decreased, leading to impaired glucocorticoid-mediated negative feedback of the HPA axis, resulting in lack of pleasure and social aversion ( 54 ). Furthermore, a previous study in a Chinese population also demonstrated a significant “U”-shaped trend between BMI and depression ( 55 ), consistent with the direction of our RCS results.…”
Section: Discussionsupporting
confidence: 92%
“…In obese patients, however, levels of leptin are decreased, leading to impaired glucocorticoid-mediated negative feedback of the HPA axis, resulting in lack of pleasure and social aversion ( 54 ). Furthermore, a previous study in a Chinese population also demonstrated a significant “U”-shaped trend between BMI and depression ( 55 ), consistent with the direction of our RCS results.…”
Section: Discussionsupporting
confidence: 92%
“…Physical status may contribute to depressive symptoms ( 48 ). According to previous studies, the relationship between depression and BMI is U-shaped ( 55 , 56 ), indicating that both underweight and overweight individuals had a higher incidence of depression, and we observed a higher incidence of depressive symptoms among underweight adults; however, no participant was classified as overweight (BMI ≥25 kg/m 2 ) in this study. Regarding alcohol consumption, the non-drinking group had a higher incidence of depressive symptoms.…”
Section: Discussionsupporting
confidence: 49%
“…Since inverse relationships between the BMI and symptoms of depression are well documented for underweight patients, an adjustment of the findings for the BMI is mandatory [ 25 , 26 ]. We found no significant differences in alpha and beta diversity measurements between groups of higher and lower symptom severity levels for depression and anxiety after adjusting for the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, both authors pointed out the significant correlation of depression [ 23 ] and anxiety [ 23 , 24 ] with the body mass index (BMI) in these studies. For the general population, a U-shaped curve for the relation between BMI and depression has been reported [ 25 , 26 ]. Regarding the underweight range, this implies that depression symptoms are high in severe underweight and decline with increasing body weight.…”
Section: Introductionmentioning
confidence: 99%